Percutaneous pinning with interphalangeal joint locked in phalanx fractures: The surgical technique and the results. Issue 31 (6th August 2021) - Liu, Shibo; Sun, Bo; Wang, Pei; Fu, Shijie
Abstract: Background: The purpose of the study was to compare the operation time, the fracture healed time, the postoperative function recovery between the techniques that temporary locking of the interphalangeal joint and traditional manual reduction in the treatment of percutaneous pinning of the phalanx fractures. Methods: Patients with phalanx fractures from January 2015 to January 2018 who were admitted to our hospital were retrospectively reviewed. Patients received surgery with traditional manual or temporary locking of the interphalangeal joint reduction. The information of patients, including age, gender, the length of the operation, the fracture healed time, the postoperative function recovery, complication, and length of postoperative hospital stay, was collected. All of the information were evaluated and compared between the 2 groups. All of the surgery were performed by 2 experienced hand surgeons of our department. The patients in the 2 groups were followed up for an average of 6 months after surgery. Results: All patients completed the operation and were followed up completely. There was no significant difference in baseline data between the 2 groups ( P > .05). The observation group who received surgery with the interphalangeal joint locked technique had significantly shorter in operative time than the control group ( P < .05). And postoperative complications in the observation group were significantly less than those in the control group ( P < .05). However, the postoperative functional recovery in both groups was no significant difference between the 2 groups ( P > .05). And there were no significant differences in the fracture healed time and length of postoperative hospital stay between the 2 groups ( P > .05). Conclusion: Both surgical techniques can enable patients to achieve good function, but the technique of interphalangeal joint locked is effective in the treatment of the phalanx fractures, as it is characterized by short operations and a quick recovery. However, this technique is only suitable for extra-articular phalanx fractures that the AO/ASIF classification of type A2.3 and less than 2 weeks, not for other phalanx fractures.